2011
DOI: 10.1097/pcc.0b013e3182231220
|View full text |Cite
|
Sign up to set email alerts
|

A spontaneous breathing trial with pressure support overestimates readiness for extubation in children

Abstract: A spontaneous breathing trial using pressure support set at higher levels for smaller endotracheal tubes overestimates readiness for extubation in children and contributes to a higher failed extubation rate. The objective data obtained during an extubation readiness test may help to identify patients who will benefit from extubation to noninvasive ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
1
31
0
8
Order By: Relevance
“…Our findings mirror those of Kurachek et al (6) who showed that the rate of extubation failure goes up markedly after 48 hours (8.2%) and 10 days (17.5%) of ventilation in a general PICU cohort. Several previous investigations demonstrate the limitations of spontaneous breathing trials in critically ill children (13, 14) to predict successful transition from mechanical ventilation. Patients ventilated for prolonged periods in the CICU are more likely to suffer from clinically significant cardiovascular dysfunction compared with the general PICU population, which may also limit successful unassisted respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings mirror those of Kurachek et al (6) who showed that the rate of extubation failure goes up markedly after 48 hours (8.2%) and 10 days (17.5%) of ventilation in a general PICU cohort. Several previous investigations demonstrate the limitations of spontaneous breathing trials in critically ill children (13, 14) to predict successful transition from mechanical ventilation. Patients ventilated for prolonged periods in the CICU are more likely to suffer from clinically significant cardiovascular dysfunction compared with the general PICU population, which may also limit successful unassisted respiration.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, performing the SBT with the pressure support set at a higher level for a smaller endotracheal tube can overestimate readiness for extubation in children. 19 The responses to our survey reflect the uncertainty regarding the performance of SBTs. In adults an elevated RSBI predicts failure, 15,16 whereas in children the performance and outcomes of RSBI are under debate.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of readiness for extubation from mechanical ventilation in critically-ill infants and children in general continues to be challenging for pediatric intensive care providers [6]. In the adult population, measures of pulmonary function and weaning indices have been developed and standardized to increase the likelihood of extubation success, but the results from applying similar weaning indices in pediatric patients have been inconsistent [7][8] and have not been readily implemented by current pediatric critical care physicians [9].…”
Section: Introductionmentioning
confidence: 99%